The ABI5-dependent down-regulation of mitochondrial ATP synthase OSCP subunit facilitates apple necrotic mosaic virus infection - He, Chengyong; Xing, Fei; Liang, Jiahui; Zhang, Zhixiang; Zhan, Binhui; Habili, Nuredin; Wang, Hongqing; Li, Shifang (Journal of experimental botany, 2023)
Apple necrotic mosaic virus (ApNMV) is associated with apple mosaic disease in China. However, the mechanisms of ApNMV infection, as well as host defence against the virus, are still poorly understood. Mitochondrial ATP synthase plays a fundamental role in the regulation of plant growth and development. However, mitochondrial ATP synthase function in response to virus infection remains to be defined. In the present study, a yeast two-hybrid (Y2H) screening revealed that the apple mitochondrial ATP synthase oligomycin sensitivity-conferring protein (OSCP) subunit (MdATPO) interacts with ApNMV coat protein (CP). It was further verified that overexpression of MdATPO in Nicotiana benthamiana inhibited viral accumulation. In contrast, silencing of NbATPO facilitated viral accumulation, indicating that ATPO plays a defensive role during ApNMV infection. Further investigation demonstrated that ApNMV infection accelerated abscisic acid (ABA) accumulation, and ABA negatively regulated ATPO transcription, which was related to the ability of ABA insensitive 5 (ABI5) to bind to the ABA-responsive elements (ABREs) of the ATPO promoter. Taken together, our results indicated that transcription factor ABI5 negatively regulated ATPO transcription by directly binding to its promoter, leading to the susceptibility of apple and N. benthamiana to ApNMV infection. The current study facilitates a comprehensive understanding of the intricate responses of the host to ApNMV infection.